2015
DOI: 10.1155/2015/503109
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approaches to Chronic Pancreatitis

Abstract: Chronic pancreatitis is a progressive inflammatory disease resulting in permanent structural damage of the pancreas. It is mainly characterized by recurring epigastric pain and pancreatic insufficiency. In addition, progression of the disease might lead to additional complications, such as pseudocyst formation or development of pancreatic cancer. The medical and surgical treatment of chronic pancreatitis has changed significantly in the past decades. With regard to surgical management, pancreatic head resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“… 7 Further research is required to answer a number of questions in regards to endoscopic stenting. 5 Many randomized controlled trials have been performed to determine optimal surgical treatment, 6 although these trials are still beset by problems with patient selection, timing of intervention and assessment of pain. Total pancreatectomy and auto islet transplantation is a promising surgical option that has yet to be widely adopted, and for which further evidence is required regarding its role in relation to other surgical treatments.…”
Section: Pre-requisites For Future Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Further research is required to answer a number of questions in regards to endoscopic stenting. 5 Many randomized controlled trials have been performed to determine optimal surgical treatment, 6 although these trials are still beset by problems with patient selection, timing of intervention and assessment of pain. Total pancreatectomy and auto islet transplantation is a promising surgical option that has yet to be widely adopted, and for which further evidence is required regarding its role in relation to other surgical treatments.…”
Section: Pre-requisites For Future Clinical Trialsmentioning
confidence: 99%
“…This disagreement appears to derive from entrenched practice and the lack of high-quality evidence. It is not helped by contradictory guideline recommendations 2 , 3 , 4 and opinion, 5 , 6 ostensibly drawn from the same evidence base and used to justify the highly variable practice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients treated with Frey procedure had longer mean survival time (14.5 ± 0.8 versus 11.3 ± 0.8 years; p = 0.037). Previously published trials also showed that organ sparing procedures such as Frey or Beger procedures yield better outcome than more aggressive treatment with PD [ 13 ]. Thus, not only should the ideal biomarker of PDAC be detectable on the early stage of carcinogenesis, but also it should be highly accurate as patients with benign lesions greatly benefit from organ sparing surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pancreatitis (CP) is an irreversible and progressive pancreatic disease caused by inflammation of the exocrine tissue . CP leads to persistent abdominal or back pain, malnutrition, and even diabetes with sufficient islet damage.…”
Section: Introductionmentioning
confidence: 99%